Perfusing chemotherapy by percutaneous lung puncture “holing” for pulmonary tuberculoma—a ten-year single center experience - Yang, Shu-Hua; Zhan, Ping; Mao, Hui-Huan; Shi, Xu-Dong; Wang, Ling-Ling (Journal of Thoracic Disease, 2013)
Background: Pulmonary tuberculoma is a special form of secondary pulmonary tuberculosis, with a poor response to drug treatment. We used the method of drug administration via percutaneous lung puncture “holing” to treat pulmonary tuberculoma and observe its short- and long-term efficacy, summing up our 10-year clinical experience. Methods: A total of 54 patients with pulmonary tuberculoma were included in this study. They themselves were taken as the control group. Three to six months of conventional anti-tuberculosis treatment was conducted firstly. Then those patients with no changes of sizes in tuberculoma were recommended to receive drug administration via percutaneous lung puncture. Isoniazid (INH, 0.1 g) and amikacin (AMK, 0.2 g) were injected into tuberculoma (once or twice per week, 10 times as a course of treatment). Results: After two months of drug treatment by lung puncture, the sputum smear test showed the negative conversion rate of tubercle bacillus was 87% (13/15), and the positive conversion rate was 8% (3/39). The tuberculosis bacillus culture indicated that the negative conversion rate was 100% (7/7). The reexamination after one year showed the negative conversion rate of tubercle bacillus in the sputum smear test was 80% (4/5). About 58% (31/54) of tuberculoma disappeared or significantly reduced, in which, 40% (21/54) of tuberculoma disappeared. The tuberculoma diameter reduced from 3.6 cm × 2.8 cm to 1.7 cm × 1.1 cm on average. Side-effects included postoperative pneumothorax 9% (5/54), hemoptysis 7% (4/54) and fever 11% (6/54). A total of 34 patients were followed up for five years, and the disappearance rate of tuberculoma was up to 47% (16/34), with no recurrence. Conclusions: The drug administration via percutaneous lung puncture—“holing” in pulmonary tuberculoma takes a significant effect obviously, good short- and long-term effects and less side effects.